COMPARATIVE ANALYSIS OF THE RESULTS OF ISOLATED TOLUENE VAPORS INFLUENCE ON RAT SKELETON BONES MORPHOGENESIS AND APPLICATION OF TIOTRIAZOLINI IN THE BACKGROUND OF TOLUENE VAPOR EXPOSURE BY MEANS OF THE FACTOR ANALYSIS - Skorobogatov, A.N.; Pastukhova, V.A.; Krasnova, S.P. (World of Medicine and Biology, 2018)
The widespread use of epoxy resins by mankind in the manufacturing process of industrial and agricultural production as well as distribution of such their components as volatile components due to emissions of toxic agents into the environment, annual expanding of the natural and artificial origin toxic compounds list, running into more and more thousands, prompted us to conduct a pilot study of the musculoskeletal apparatus morphology under the influence of toluene.The purpose of the study was to compare the remote results of the toluene vapors isolated action effect and the Tiotriazolini application against the background of the toluene vapors impact on the morphogenesis of mature rats’ skeletal bones.The research was conducted on the tibial and coxal bones of mature white male rats at an early age of 3 months. The gender identity is chosen due to the fact that, unlike females, males do not have cyclical changes in their hormonal background. To assess the toluene vapors influence degree on the morphogenesis of skeletal bones as well as the input of Tiotriazolini for 60 days against this background, a single-factor dispersive analysis was carried out. The experimental animals were divided into 2 groups. The 1st group consisted of male rats who inhaled toluene every day for two months in the installation for substances inhaling with a single exposure of 5 hours where the maximum allowable concentration was 10 (500 mg / m3). The second group consisted of male rats, who daily for two months received intraperitoneally a 2.5% solution of tiotriazolini in ampules against the background of toluene inhalation.According to the single-factor analysis, the 60-days toluene vapors effect on the rats’ bodies truly influenced the indicators characterizing the bone-forming function of the proximal epiphyseal cartilages and the periosteum of the tibial bones as well as the phase composition of the coxal bones biomineral during the period between the first and the sixtieth days of the observation. And in this case the force of the acting factor influence for the majority of indicators remained at approximately the same level until the fifteenth day of the observation period, and then it gradually decreased.The experimental conditions had a significant effect on the total width of the proximal epiphyseal cartilage of the tibia from the first to the sixtieth day of the observation, and the force of the acting factor influence was respectively 58.4%, 61.7%, 63.2%, 46.2% and 25.5 %. Besides, the experimental conditions significantly influenced the width of the indifferent cartilage zone.Also, during the entire observation period the toluene vapors truly had an effect on the content of the intercellular substance in cartilage (the force of the acting factor influence was 37.9%, 37.8%, 33.4%, 14.4% and 7.9% respectively), on keeping the primary spongiosis in the osteogenesis zone (the force of influence was 16.4%, 19.7%, 12.1%, 12.3% and 7.0%), as well as on the number of osteoblasts in the osteogenesis zone (the force of influence was 31,1%, 36,2%, 18,1%, 29,8% and 11,5%).Besides, throughout the observation period, the experimental conditions had a significant impact on the osteon channels diameters, on the bone marrow cavity area and on the diaphysis compact substance area. The experimental conditions significantly influenced the indicators characterizing the phase composition of the coxal bones biomineral. At the same time, the force of the acting factor influence for the majority of indicators remained at approximately the same level until the fifteenth day of the observation period, and then it gradually decreased.The maximum force of the acting factor influence on the width of the osteogenesis zone, on keeping the intercellular substance in the epiphyseal cartilages and on the width of the osteon layer (43.3%, 37.9% and 47.7%) was recorded on the first day of the readaptation period. Also, the maximum force of the 2nd experimental group’s conditions influence on the coefficient of the coxal bone biomineral micro texturing (81.7%) was recorded on the first day of the observation. And on the fifteenth day the influence on the percentage of apatite (90.1%) was recorded.While assessing the impact of the Tiotriazolini application against the background of the 60-days toluene vapors influence on the indicators that characterize the morpho-functional state of the proximal epiphyseal cartilages of the mature white rats’ tibia, there was established the following: in relation to the parameters of the first group, the experimental conditions significantly affected the total width of the proximal epiphyseal cartilage of the tibia during the period from the first to the sixtieth day of the readaptation period, and the force of the acting factor influence was respectively 21.0%, 32.0%, 35.5%, 33.7% and 27.8%.However, the conditions of the 2nd experimental group had a significant influence on the content of the intercellular substance in cartilage in the osteogenesis zone during the period from the first to the sixtieth day of the observation (the force of the acting factor influence was respectively 9.2%, 14.5%, 19.4%, 9,8% and 6.1%, and 7.9%, 16.1%, 10.8%, 21.8% and 6.9%), as well as on keeping the primary spongiosis in the osteogenesis zone from the seventh to the sixtieth day (the force of influence was 6,2%, 7,0%, 8,9% and 9,4%). Finally, the Thiotriazoline application against the background of the toluene vapors effect on the mature white rats’ bodies had a significant impact on the number of osteoblasts in the proximal metaphysis area during the period from the first to the thirties day of the observation (the force of the acting factor influence was 7.4%, 23.9%, 28.1 % and 15.0%).The tiotriazolini use against the background of toluene vapors effect on the bodies of white rats during the period from the first to the sixtieth day of the observation had a significant effect on the total width of the diaphysis layers (the force of the acting factor influence was respectively 25.1%, 35.9%, 35.4%, 12.9%, and 18.5% respectively), on the width of the osteon layer (the force of influence was 12.4%, 22.9%, 17.9%, 5.8% and 10.9%) and on the width of the internal general plates layer (the force of influence was 6.3%, 15.3%, 10.7%, 6.6% and 5.4%). Besides, during the period from the first to the fifteenth day of the observation, the force of influence on the width of the external general plates layer was 8.3%, 9.5% and 12.5%.Also, the use of Tiotriazolini against the background of the toluene vapors effect on the mature white rats’ bodies on the seventh and the thirtieth days of the observation had a significant impact on the percentage of whitlockite: the force of the acting factor influence was 32.8% and 31.1%, and from the fifteenth to the sixtieth day the impact on the percentage of apatite and calcite was respectively 35.7%, 51.8% and 48.7%, and 28.7%, 28.5% and 26.7%.
Keywords: bones; structure; toluene; thiotriazoline; factor analysis